Rapamycin Dampens Inflammatory Properties of Bone Marrow ILC2s in IL-33-Induced Eosinophilic Airway Inflammation - Boberg, Emma; Weidner, Julie; Malmhäll, Carina; Calvén, Jenny; Corciulo, Carmen; Rådinger, Madeleine (Frontiers in Immunology, 2022)
The alarmin cytokine interleukin (IL)-33 plays an important proinflammatory role in type 2 immunity and can act on type 2 innate lymphoid cells (ILC2s) and type 2 T helper (TH2) cells in eosinophilic inflammation and asthma. The mechanistic target of rapamycin (mTOR) signaling pathway drives immune responses in several inflammatory diseases, but its role in regulating bone marrow responses to IL-33 is unclear. The aim of this study was to determine the role of the mTORC1 signaling pathway in IL-33-induced bone marrow ILC2 responses and its impact on IL-33-induced eosinophilia. Wild-type mice were intranasally exposed to IL-33 only or in combination with the mTORC1 inhibitor, rapamycin, intraperitoneally. Four groups were included in the study: saline-treated (PBS)+PBS, rapamycin+PBS, PBS+IL-33 and rapamycin+IL-33. Bronchoalveolar lavage fluid (BALF), serum and bone marrow cells were collected and analyzed by differential cell count, mediator analysis and flow cytometry. IL-33 induced phosphorylation of the mTORC1 protein rpS6 in bone marrow ILC2s both in vitro and in vivo. The observed mTOR signal was reduced by rapamycin treatment, indicating the sensitivity of bone marrow ILC2s to mTORC1 inhibition. IL-5 production by ILC2s was reduced in cultures treated with rapamycin before stimulation with IL-33 compared to IL-33 only. Bone marrow and airway eosinophils were reduced in mice given rapamycin before IL-33-exposure compared to mice given IL-33 only. Bone marrow ILC2s responded to IL-33 in vivo with increased mTORC1 activity and rapamycin treatment successfully decreased IL-33-induced eosinophilic inflammation, possibly by inhibition of IL-5-producing bone marrow ILC2s. These findings highlight the importance of investigating specific cells and proinflammatory pathways as potential drivers of inflammatory diseases, including asthma.